Effect of the cutoff wall on the fate of nitrate in coastal unconfined aquifers under tidal action - Kong, Jun; Gao, Chao; Jiang, Chaohua; Wang, Jun; Gao, Xinyu; Jing, Li (Frontiers in Marine Science, 2023)
This paper investigated the effects of the cutoff wall on the fate of nitrate (NO3-), the NO3- removal rate and the salinity distribution in a coastal aquifer under tidal action. A numerical study was performed based on a coupled model with variable-saturation and variable-density flow and a convection-diffusion-reaction equation for solute transport in a coastal unconfined aquifer. The results showed that the cutoff wall led to a larger upper salinity plume (USP) and that the saltwater wedge (SW) further retreated seaward. The recirculation pathways of saltwater and groundwater were largely modified by the wall. The cutoff wall within the tidal range could increase the NO3- mass of denitrification and the NO3- removal efficiency and decrease the length of the SW and the freshwater flux. This modification of the saltwater and groundwater recirculation pathways was enhanced with increasing wall depth. A deeper cutoff wall led to a further retreated SW, lower freshwater flux, and greater improvements in the NO3- mass of denitrification and the NO3- removal efficiency. In addition, the cutoff wall significantly decreased the terrestrial dissolved organic carbon (TDOC) discharge into the sea. Dissolved organic carbon source (SDOC) promoted a higher NO3- removal efficiency. This study provides us with a better understanding of coastal physical-biogeochemical processes and dynamic mechanisms, as well as a guide for designing engineering measures to mitigate NO3- contamination and thus enhance groundwater quality management.